Effect of Using Kangaroo Mother Care on the Sleep State and Physiological Parameters Among Preterm Neonates - Helaly, Nadia Medany; Mohammed, Abeer Abd El-Razik Ahmed (International Journal For Research In Health Sciences And Nursing, 2020)
Kangaroo Mother Care (KMC)refers to the care of the preterm neonates carried skin-to-skin with the mother. Early, prolonged and continuous mother- neonate contact provides exclusive breastfeeding and improves maternal–neonate bonding as well.It also guards against bradycardia and apneic episodes. In addition, it provides stability of transcutaneous oxygen level. Moreover, it improvesthe maturation of the prefrontal cortex and facilitates better organization of sleep pattern. Aim of the study was to determine the effect of using KMC on the sleep state and physiological parameters among preterm neonates. ResearchDesign:A quasi experimental research design was used. Setting: This study was conducted at the NICU ofMaternity University Hospital at El-Shatbyin Alexandria. Subjects:A convenient sample of 60 preterm neonates and their mothers attending the previously mentioned setting. The preterm neonates fulfilled the following criteria: Feeder and grower as well asgestational age ranged from 32-<37 weeks were equally divided into a study group (received KMC intervention plus routine NICU care) and a control group (received NICU routine care in conventional position inside the incubator). Tools: Two tools were used tocollect necessary data namely;Characteristics of the Mothers and the Preterm Neonates and Medical History of the Preterm Neonatesas well asPreterm Neonates’Sleep State Assessment Observational Checklist. Results: The mean heart rates after KMC of the preterm neonates in the study group were lower than the mean heart rates of those in the control group after the conventional position inside the incubator (144.39±13.98 and 159.93 ± 22.98 respectively) and the differences were statistically significant (P= 0.001). Additionally, the mean preterm neonates’ respiratory rates were 45.92 ± 4.85 after KMC compared to 54.56 ± 6.07 of those in the control group with statistical significant differences, where P<0.001. Moreover, the mean oxygen saturations of preterm neonates in the study group after KMC were higher than the mean oxygen saturations of those in the control group (97.70 ± 0.93 and 94.93 ± 18.3 respectively) and the differences were statistically significant (P<0.001). Additionally, 80.0% of the preterm neonates in the study group were in deep sleep state compared to 33.3% of those in the control group. Highly aroused and agitated/crying state was found among 43.3% of the preterm neonates in the control group compared to none of those in the study group and the differences were statistically significant (P= 0.000). Conclusion:It can be concluded that KMC was effective in improving the sleep state and the physiological parameters of the preterm neonates. Recommendation: ApplyingKMC for all preterm neonates as a part of routine care within NICU.